Tahapan Pemberdayaan Perempuan dalam Pengelolaan Sampah di Kabupaten Bandung - Sekarningrum, Bintarsih; Lukmanul H, Rahmatika Mutiara Atsalitsa; Yunita, Desi (Jurnal Sosiologi Andalas, 2024)
Abstract: This study aims to describe the stages of women's empowerment in waste management through waste banks analyzed from the concept of empowerment stages. The research uses a qualitative method. The results show that the stages of women's empowerment consisted of: (1) raising awareness about waste problems; (2) providing training and skills on waste processing and the formation and development of Bank Sampah Unit (BSU); and (3) increasing women's participation in running the Bank Sampah Unit (BSU) independently. However, the field findings show that in the capacity stage, women already can develop the organization (BSU). It is concluded that the stages of women's empowerment in waste management through waste banks have made women empowered in managing waste in their households.